2013
DOI: 10.1016/j.celrep.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of 5-Hydroxymethylcytosine and Chromatin Marks in Mammalian Neurogenesis

Abstract: SUMMARY DNA methylation in mammals is highly dynamic during germ cell and pre-implantation development but is relatively static during development of somatic tissues. 5-hydroxymethylcytosine (5hmC), created by oxidation of 5-methylcytosine (5mC) by Tet proteins and most abundant in brain, is thought to be an intermediate towards 5mC demethylation. We investigated patterns of 5mC and 5hmC during neurogenesis in the embryonic mouse brain. 5hmC levels increase during neuronal differentiation. In neuronal cells, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

37
389
5
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(444 citation statements)
references
References 33 publications
37
389
5
5
Order By: Relevance
“…During development, TrxG and PcG complexes at bivalent domains play a key role in fine-tuning the expression of genes encoding crucial factors and in defending against unscheduled gene activation (57). Differentiation of neural progenitors is accompanied by an epigenetic switch characterized by a decrease of H3K27me3 and a gain of H3K4me3 at the promoters of proneural genes (6). Exogenous SOX2 expression previously was shown to be sufficient to reprogram fibroblasts into multipotent neural stem cells (NSCs) (55) or, in combination with Mash1, to reprogram human brain pericytes into neuronal cells (58).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During development, TrxG and PcG complexes at bivalent domains play a key role in fine-tuning the expression of genes encoding crucial factors and in defending against unscheduled gene activation (57). Differentiation of neural progenitors is accompanied by an epigenetic switch characterized by a decrease of H3K27me3 and a gain of H3K4me3 at the promoters of proneural genes (6). Exogenous SOX2 expression previously was shown to be sufficient to reprogram fibroblasts into multipotent neural stem cells (NSCs) (55) or, in combination with Mash1, to reprogram human brain pericytes into neuronal cells (58).…”
Section: Discussionmentioning
confidence: 99%
“…In NPCs, the chromatin regions of proneural and neurogenic genes contain high levels of both H3K27me3 and H3K4me3 (37,38); such bivalent marks maintain the genes transcriptionally silent but poised for activation once differentiation cues are received (32). To understand the regulatory function of SOX2 in activation of the neurogenic program, we examined previously published ChIP-sequencing (ChIP-seq) data including the occurrence of H3K27me3 and H3K4me3 marks at SOX2-binding sites in mouse ES cell-derived NPCs (6,26). Genomewide analysis revealed that of the 16,683 SOX2-binding sites, 2,514 were enriched for H3K27me3 (15.1%) (Fig.…”
Section: Sox2 Deficiency Leads To Epigenetic Repression At the Promotersmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Hydroxymethylation of cytosines has been suggested to play an important role in neurons due to the abundance of this mark in the brain (Hahn et al 2013;Rudenko et al 2013). Therefore, we hypothesized that this epigenetic mark might also be critical for the proliferation and/or differentiation of intestinal epithelial cells.…”
Section: The 5hmc Mark Is Prominent In Intestinal Villus Epithelial Cmentioning
confidence: 99%
“…5-hmC is highly enriched in the adult brain (7), dynamically regulated by neural activity (8), and accumulates across the lifespan (9). This epigenetic mark is critically involved in neuronal differentiation and in the reprogramming of pluripotent stem cells (10), and rather than being an intermediate state of active DNA demethylation, 5-hmC can be either dynamic or stable (8,10). Unlike its repressive cousin, 5-mC, which is primarily found along CpG-rich gene promoters, 5-hmC is enriched within gene bodies and at intronexon boundaries of synaptic plasticity-related genes, as well as within distal cis-regulatory elements, which together point to an important role for 5-hmC in coordinating transcriptional activity (11)(12)(13).…”
mentioning
confidence: 99%